Development of alternative models for early detection of religiously legitimated anarchism in Bali Province - Handayani, Ni Nyoman Lisna (Jurnal Civics: Media Kajian Kewarganegaraan, 2022)
The long-term goal of this research is to develop a model for preventing radicalism in the Bali Region. This research used a front-ended prototype studies development approach. The data in this study were collected by: (1) observation guidelines, (2) clinical interview guidelines, (3) questionnaires, (4) document study guidelines, (5) focus groups discussion, and (6) interrater validity factors. Data analysis will be carried out using the EFA and SMART methods combined with SaSHA (satisfication stake holders appraisal) analysis. The research products consist of: (1) mapping of social modalities and cultural modalities of traditional villages, (2) mapping of potential strengths and weaknesses of each traditional village, (3) profile of each traditional village, (4) preliminary model for preventing radicalism and terrorism based on local values and institutions.